Integrated Marketing Communication Pada Nasi Kulit Malam Minggu - Wa’dah, Habibatul; Muksin, Nani Nurani (PT Literasi Nusantara Publisher, 2023)
This study aims to determine Integrated Marketing Communication on Nasi Kulit Malam Minggu to: a) Advertising on Nasi Kulit Malam Malam Minggu, b) Public Relations on Nasi Kulit Malam Malam Minggu, c) Personal Selling on Nasi Kulit Malam Malam Minggu, d) Sales Promotion on Saturday Night Rice Saturday Night Leather, e) Direct Marketing on Saturday Night Skin Rice. This study uses the concept and theory of Integrated Marketing Communication which consists of Advertising, Public Relations, Personal Selling, Direct Marketing. This research approach is descriptive qualitative method. The data collection technique used was in-depth interviews. Integrated Marketing Communication for Nasi Kulit Malam Malam Minggu is by advertising on social media Instagram and Facebook, using media partners, brand partners, influencers, cabbage, activities on social media pages and websites, press conferences or direct coverage by inviting media partners, and participating in events. in Public Relations activities, offering and selling products directly through staff in the field on personal selling, conducting sales promotions on online delivery applications and also certain seasonal promos on holiday events, maximizing social media to provide information related to existing promotions on direct marketing carried out.